Pengaruh Pengetahuan Perpajakan, Kesadaran Wajib Pajak dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Wijaya, Anis Boedi; Wijaya, Indra (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to examine the effect of individual taxpayer compliance at West KPP Pratama Bekasi. The independent variables in this study are Tax knowledge, taxpayer awareness, and quality of tax service while the dependent variable is individual taxpayer compliance. This study uses a survey method by providing questionnaires to taxpayers registered at West KPP Pratama Bekasi Barat. The sample determination uses the Random Sampling Technique method, then the manual questionnaire data on the hard file is inputted into excel and analyzed by multiple linear regression using SPSS Version 26. The number of samples in this study is 100 respondents from the total population. The results of the regression test show that tax knowledge and quality of tax service have a positive effect on individual taxpayer compliance, while taxpayer awareness does not affect individual taxpayer compliance at west KPP Pratama Bekasi.